KEPEDULIAN SOSIAL MASYARAKAT PERBATASAN DALAM MEMPERTAHANKAN KETAHANAN EKONOMI (KASUS DI TEMAJUK, PALOH, SAMBAS KALIMANTAN BARAT) - Fatmawati Fatmawati; Indah Sulisdiani; Marini Marini; Syarmiati Syarmiati (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2024)
Local wisdom of social care is the culture of helping one another to build food resilience in the Malay community in the border of Temajuk district of Sambas. For the Malay community to be a professional farmer, abundant food resources can survive without dependence on others. This research uses qualitative discrepancy methods by demonstrating food sustainability in a cultural perspective. The results of the study explained that social concerns have helped a former Indonesian labour force citizen who returned to his hometown to stop living in Serawak Malaysia so that he did not have a fixed job and decided to become a farmer. Social care is a form of support of the Malay people to others against each other voluntarily, through the approach of social capital such as economic resilience assistance through the provision of productive land and trade networks with neighbouring countries, thus creating resiliency with the community at the Temajuk border.